Zastosowanie kartograficznego systemu informacji w waloryzacji przyrodniczej na przykładzie gminy Tarnowo Podgórne - Kubiak, Jarosław; Ławniczak, Radzym (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2009)
In the present research work it is showed the available cartographic resources which find practical application, particularly, in the works within the sphere of regional planning. It is confined to the ones which are made accessible by the government, trade offices or educational establishments. There are presented the ones which are published on the basis of technical instruction which determinate recurrence in respect of theme regardless of place, time and the author study. There have been taken into consideration cartographic materials in the analogue and numerical form. There are presented the topographic maps in system "65", "92", topographical data base, VMapL2, geological maps, soil-agricultural maps, hydrographie maps and sozological maps. The above mentioned materials were used in eco-physiographic study for Tarnowo Podgórne Community. The studies are documentations written out to needs of regional planning and studies which describe particular components of natural environment and their interrelationships. The final effect of this work was to determine usefulness of community area for the invest needs. In the synthetic way, in the cartographic form, there was presented the helpfulness of analyzed components. There was obtained the spatial layout of putting together value of analyzed parameters and afterwards the areas were classified. The classification allows to show terrains which are the most advantageous for the definite directions of management, in the case of the present study - for building purposes.